The Importance of the Narodna Prosveta Publishing House and Its Founder Anatoly Ivanovich Pritzker in the History of Yugoslav Book Publishing - Božović, Ivana N. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The aim of this paper is to present the publishing idea of a Russian émigré, which proved to be an exceptional contribution to Serbian culture. This publishing endeavour was a rather unique one given the fact that unlike the abundant publishing activity of Russian emigration, which was primarily intended for Russian readers, the Narodna Prosveta Publishing House was primarily focused on Serbian culture, on two bases: it was made up of Serbian cultural activists and, above all, intended for Serbian readers. The status of the Narodna Prosveta in the history of Serbian book publishing has been burdened by unfounded charges against its founder A. I. Pritzker on suspicion of collaboration with the German occupier, as well as the absence of a well-deserved critical register – which is an additional motive to restore the Narodna Prosveta after a long period of silence to its rightful place – at the core of the interwar publishing and cultural activities.